2020
DOI: 10.7717/peerj.9580
|View full text |Cite
|
Sign up to set email alerts
|

Viable bacterial communities on hospital window components in patient rooms

Abstract: Previous studies demonstrate an exchange of bacteria between hospital room surfaces and patients, and a reduction in survival of microorganisms in dust inside buildings from sunlight exposure. While the transmission of microorganisms between humans and their local environment is a continuous exchange which generally does not raise cause for alarm, in a hospital setting with immunocompromised patients, these building-source microbial reservoirs may pose a risk. Window glass is often neglected during hospital di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Overall, we sought to identify the potential utility of the AerosolSense device for active air environmental surveillance and used a healthcare setting as the testbed. The active air samples recovered were compared to the current standard for indoor environmental surveillance, flocked environmental swabs and passive air settling plates [64][65][66][67] . We confirmed the results of previous studies that demonstrated significant environmental contamination by SARS-CoV-2 in rooms occupied by COVID-19 positive patients 14,50,54,64,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we sought to identify the potential utility of the AerosolSense device for active air environmental surveillance and used a healthcare setting as the testbed. The active air samples recovered were compared to the current standard for indoor environmental surveillance, flocked environmental swabs and passive air settling plates [64][65][66][67] . We confirmed the results of previous studies that demonstrated significant environmental contamination by SARS-CoV-2 in rooms occupied by COVID-19 positive patients 14,50,54,64,68 .…”
Section: Discussionmentioning
confidence: 99%